Understanding the impact of personalized recommendations on customer satisfaction, likelihood to recommend and repurchase intentions - Rodrigues, Joana Paixão Simões Nunes (2021)
The present dissertation aims to study the impact of personalized recommendations components’ and customers perceptions towards it on customer satisfaction with recommendations. These include explanation of the suggested items, fit with the customer, and privacy concerns, and trust in the retailer issuing the recommendation, respectively. Then, the influence of satisfaction with recommendations on customer satisfaction with product choice is analysed. Additionally, the effect of these two constructs on the likelihood to recommend the retailer and repurchase intentions is studied. This thesis employed an online survey to conduct the mentioned analysis. The questionnaire asked respondents to recall the last time they received a personalized recommendation and purchased the suggested product. Results show that explanation, fit, and trust positively influence satisfaction with recommendations, whereas privacy concerns negatively impact the latter. Satisfaction with recommendations proved to positively influence customer satisfaction with the product choice, consequently leading to a higher likelihood to recommend the retailer and later generating increased repurchase intentions. An additional analysis focused on the difference in behaviour between the models of low and high involvement products. In general, the latter had a higher explanatory power than the former. Concluding, the findings reveal the importance of the personalized recommendations’ attributes on satisfaction with these suggestions, affecting customer satisfaction, and customer loyalty, relevant measures of customer feedback for firms. Thus, retailers should provide users with personalized options on their digital platforms to boost their relationship with customers. The stated options should focus on satisfying users regarding the recommendations’ components and customer perceptions.